Seeking socio-cultural relevance in Sarawakian literature in English through synchonic thematic clustering - Yeoh, Patrick Peng Sim (2012)
This study investigates the extent and nature of local Sarawakian literature in English (SLIE) across genres from folktales and Praise Songs translated into or retold in English, to anecdotes, short stories and poems written originally in English by Sarawakians, particularly from the 1960s to the first decade of the 21st century. It first of all attempts to define Malaysian Literature, followed by Malaysian Literature in English (MLIE) and discusses the relevant political factors that led to the classification of National Literature and Sectional Literature. Sarawakian Literature in English (SLIE) is then defined, followed by a discussion of the possible factors that led to Sarawakian literature in English to be practically completely ignored in mainstream discourse on Malaysian literature in English (MLIE), looking at the issue from political and socio-cultural perspectives. Significant and relevant factors that have led to differences between Sarawakian literature in English and mainstream Malaysian literature in English are investigated and explained. The catalytic role of the Borneo Literature Bureau (BLB) in the development of SLIE is also explained. The study takes a thematic approach in reading, analysing and interpreting the selected multi-genred texts, linking them within „synchronic thematic clusters‟ or „landscapes‟ to achieve a more focused socio-cultural commentary of Sarawakian society, past and present. The texts studied are divided into „derivative” and contemporary or original Sarawakian literature in English, and analysed using the hermeneutics approach, for a better understanding of their relevance to the main study objective, which is to prove that Sarawakian literature in English is socio-cultural commentary. This study shows that while Sarawakian society may have changed and developed over the past century or so from the advent of White Rajah rule in 1841 to the early years of the 21st century, the different eras are linked by common themes of affinity with the land and Nature, a strong pioneering spirit, harmonious communal living and the will to survive under sometimes difficult circumstances. This pioneering study on Sarawakian literature in English arrives at the conclusion that Sarawakian literature in English not only exists but is also fairly substantial although it differs from mainstream MLIE in many literary, social and cultural aspects. It is hoped that this pioneering study will be a catalyst for further research in Sarawakian Literature in English.